Novel hydroxyapatite-based bio-ceramic hollow fiber membrane derived from waste cow bone for textile wastewater treatment - Hubadillah, S.K. (Elsevier B.V., 2020)
Industrial textile wastewater is toxic due to the presence of recalcitrant color pigments and poisonous heavy metals. In this study, the hydroxyapatite (HAp)-based bio-ceramic hollow fiber membranes (h-bio-CHFM) were developed via the combined phase inversion and sintering technique. It was found that the properties of the developed h-bio-CHFMs were greatly affected by the HAp content of the ceramic suspension, and sintering temperature. The h-bio-CHFM with the sintering temperature of 1200 Â°C exhibited the long rod-shaped HAp particles and the smallest pore size (0.013 Î¼m). High removals of color (99.9), COD (80.1), turbidity (99.4) and conductivity (30.1) were achieved using the h-bio-CHFM sintered at 1200 Â°C with stable high flux of 88.3 L/m2h. Remarkably, the h-bio-CHFM sintered in the temperature range of 1000â1200 Â°C also demonstrated excellent adsorption ability towards heavy metals with 100 removals. The results of this study show the potential of the h-bio-CHFM for the efficient industrial textile wastewater treatment applications. Â© 2019 Elsevier B.V.